Development of Compact Disc (CD) Learning Media Program for Basic Chemistry Course at IAIN Kerinci - Tri Saslina (IAIN Batusangkar, 2022)
: Basic Chemistry is a compulsory subject in Biology Tadris at IAIN Kerinci, which studies the physical changes of material in the separation of mixtures, namely filtration, distillation, sublimation, recrystallization, and chromatography. With the lecture method, in this material, we cannot see directly the changes that occur, so that in this material a practicum is needed to see firsthand the changes that occur. At IAIN Kerinci, there is no special laboratory for chemistry to carry out practicum. Therefore we need media that can describe these changes, so that it will lead to student learning motivation. The purpose of this research was to make learning media in the form of a CD program that will be used in learning basic chemistry of mixed separation materials and to determine the level of validity and practicality of chemistry learning media in the form of a CD program for mixed separation materials. The methodology used in this research was the type of research, development procedures, test subjects, data types, data collection instruments, data analysis techniques. The results of this study indicated that the CD Program learning media on mixed separation materials can be used as suitable learning media for learning chemistry of mixed separation materials in the basic chemistry course in the biology tadris department of IAIN Kerinci, and the CD Program media on mixed separation materials developed is valid. and has been practically used in learning.